Consumer Buying Behavior towards Daraz Nepal - Shrestha, Aayush (Nepalese Journal of Business, 2025)
This study examines the consumer buying behavior towards Daraz Nepal. Consumer buying behavior is the dependent variable. The selected independent variables are price, delivery, discount, past experience, and product availability. The primary source of data is used to assess the opinions of respondents regarding price, delivery, discount, past experience, product availability, and consumer buying behavior. The study is based on primary data from 125 respondents. To achieve the purpose of the study, a structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of consumer buying behavior towards Daraz Nepal. The study showed a positive impact of price on consumer buying behavior. It indicates that affordable pricing policy leads to increase in consumer buying behavior. Similarly, the study showed a positive impact of delivery on consumer buying behavior. It indicates that fast delivery service leads to increase in consumer buying behavior. Likewise, the study also revealed a positive impact of discount on consumer buying behavior. It indicates that different discount schemes lead to increase in consumer buying behavior. Further, the study observed a positive impact of past experience on consumer buying behavior. It indicates that knowledge and understanding gained from previous encounters lead to change in consumer buying behavior. In addition, the study observed a positive impact of product availability on consumer buying behavior. It indicates that easy availability of product leads to increase in consumer buying behavior.